KOMUNIKASI ANTAR PRIBADI BAGIAN PEMBINA DI BALAI BESAR REHABILITASI SOSIAL BINA DAKSA ( BBRSBD ) PROF. DR. R. SOEHARSO SURAKARTA DALAM MELAKUKAN PELAYANAN SISWA - Jarot, Faizal (KOMUNITAS, 2014)
Interpersonal communication is a communication process happened between two or more people with direct face to face. As the most complete and the most perfect communication, interpersonal communication is very potential to influence or to persuade others so that interpersonal communication plays important role in human life. This study aims to know the interpersonal communication on elder at BBRSBD Prof. DR. R. Soeharso Surakarta in students service. This study uses qualitative methods. The primary data is information about the pattern of inter- personal communication between official elder with students in BBRSBD Prof. DR. R. Soeharso Surakarta in student services. These data were collected throughinterview method with the elder supervisors, officials and student BBRSBD Prof.DR. R. Soeharso Surakarta. The results shows that official elder in BBRSBD Prof. DR. R. Soeharso Surakarta provides counseling services to the students trough rehabilitation guidance and motivation by using interpersonal communication either verbal or nonverbal even verbal and non-verbal simultaneously. Verbal communication is a communication that is done by oral or written. Particularly, the use of verbal communication in the form of Indonesian language and writing, it can be seen when the elder officer providing services to students trough guidance. Non-verbal communication is communication without using words or nonlinguistic. The use of non-verbal communication in BBRSBD Prof. DR. R. Soeharso Surakarta is a siren sound (as mark in starting a meal), image symbol of wheelchairs and hand movements showing a certain direction or command. Meanwhile, verbal and non-verbal communication simultaneously used by elder in BBRSBD Prof. DR. R. Soeharso Surakarta is Indonesian language followed by the hand movement, for example in serving students who are physically disabled and speech impaired at the same time